Association between treatment duration and mortality or relapse in adult patients with Staphylococcus aureus bacteraemia: a retrospective cohort study. (May 2020) - Abbas, M.; Rossel, A.; de Kraker, M.E.A.; von Dach, E.; Marti, C.; Emonet, S.; Harbarth, S.; Kaiser, L.; Uçkay, I.
Abstract: Objectives: The aim was to evaluate the effect of duration of therapy (DOT) on mortality and relapse for patients with Staphylococcus aureus bacteraemia (SAB). Methods: We performed a retrospective single-centre cohort study including adult patients with SAB. We determined the association between DOT (≤14 days versus >14 days) and mortality by adjusted hazard ratios (aHR) and 95% confidence intervals through Cox regression adjusted for immortal-time bias and confounding by indication, stratified by presence of complicated SAB (any of: endocarditis, implant, duration of SAB >2 days, fever >3 days). The primary outcome was 90-day all-cause mortality, and the secondary outcome was 90-day relapse. Results: Between January 2010 and December 2015, we included 530 patients, of whom 94 out of 530 (17.7%) had methicillin-resistant SAB and 305 out of 530 (57.6%) had complicated SAB. Ninety-day mortality was 27.0% (143/530), with no significant trend across the study period; median time to death was 17 days (interquartile range (IQR) 8–30) after onset of SAB. Median DOT was 20 days (IQR 13–39). Patients with complicated SAB had significantly reduced mortality with DOT >14 days (aHR 0.32, 95% CI 0.16–0.64). DOT was not associated with mortality in patients with uncomplicated SAB (aHR 0.85; 0.41–1.78). Eighteen (18/530) patients (3.4%) relapsed; on univariate analysis, DOT was not associated with relapse (HR 1.01; 0.97–1.06). Conclusions: DOT >14 days is associated with higher survival in patients with complicated SAB, but not for patients with uncomplicated SAB. No association was found for relapse, but 90-day relapse was very low in this cohort. Importantly, 90-day mortality remained high across the study period.